Bayesian Morphological Clock versus Parsimony: An Insight into the Relationships and Dispersal Events of Postvacuum Cricetidae (Rodentia, Mammalia). (23rd July 2021) - López-Antoñanzas, Raquel; Peláez-Campomanes, Pablo
Abstract: Establishing an evolutionary timeline is fundamental for tackling a great variety of topics in evolutionary biology, including the reconstruction of patterns of historical biogeography, coevolution, and diversification. However, the tree of life is pruned by extinction and molecular data cannot be gathered for extinct lineages. Until recently methodological challenges have prevented the application of tip-dating Bayesian approaches in morphology-based fossil-only data sets. Herein, we present a morphological data set for a group of cricetid rodents to which we apply an array of methods fairly new in paleontology that can be used by paleontologists for the analysis of entirely extinct clades. We compare the tree topologies obtained by traditional parsimony, time-calibrated, and noncalibrated Bayesian inference phylogenetic approaches and calculate stratigraphic congruence indices for each. Bayesian tip-dated clock methods outperform parsimony in the case of our data set, which includes highly homoplastic morphological characters. Regardless, all three topologies support the monophyly of Megacricetodontinae, Democricetodontinae, and Cricetodontinae. Dispersal and speciation events inferred through Bayesian Binary Markov chain Monte Carlo and biodiversity analyses provide evidence for a correlation between biogeographic events, climatic changes, and diversification in cricetids. [Bayesian tip-dating; Cricetidae; Miocene; morphological clock; paleobiodiversity; paleobiogeography; paleoecology; parsimony; STRAP.]